Quasi-linear transport analysis of impurity mode in tokamak plasmas - M.K. Han; J.Q. Dong; W. Horton; Z.X. Wang; X.R. Duan; W.L. Zhong; X.L. Zou; A.P. Sun; J. Li; Y. Shen; L.F. Wang (Nuclear Fusion)
The quasilinear turbulent particle and heat transports induced by the impurity mode (IM), driven by the opposite gradients of the core hydrogen and outer $C^{6+}$ , $O^{6+}$ , $O^{8+}$ and $Ne^{8+}$ ions, are shown to be crucial for plasma confinement in toroidal magnetic configurations. Full gyrokinetic effects of both the main and impurity ions, derived from the kinetic theory, are taken into account. Even in the absence of ion temperature gradient or trapped electron (TE) effects, IM turbulence induces significant particle and heat transports, when the impurity fraction remains at the low levels typically measured in plasma experiment. The small mass m _z and large charge number Z ions enhance the turbulent transport induced by the IM turbulence and reduce the excitation threshold. The investigation of the temperature ratio $ {τ_s = T_e/T_s}$ effect shows that the inward impurity and outward main ion particle and heat fluxes as well as the growth rate of IM increase when τ _z increases. In contrast, the growth rate increases first and then decreases while the fluxes are all increase when τ _i increases. It is also found that the TEs mainly impact the particle transport, while the impurity ion fraction dominates the particle and thermal transports. Most importantly, the IMs are shown to produce significant outward heat transport and inward impurity transport even in regimes with relatively flat ion temperature profiles.